Himbauan Pencegahan dan Bantuan Covid-19 kepada Masyarakat Desa Gelepulo dan Desa Kelitu di Provinsi Aceh - Abdul Haris; Waridah Waridah; Siti Hawa Lubis (Pelita Masyarakat, 2022)
The COVID-19 pandemic has paralyzed people's lives in many sectors. The economy and health have been victims of the Covid-19 attack. Gele Pulo and Kelitu villages are among the villages affected by Covid-19. Public misunderstanding about the dangers of the Corona Virus and economic difficulties have been the trigger for the team to carry out community service activities. This community service activity aims to provide an explanation and understanding of the community from the dangers of Covid-19 transmission and how to overcome some of the problems that arise as a result of the Covid-19 attack in the form of counseling. The method of implementing this activity is interactive lectures and discussions with the village community who are the target of the service. The results of service activities can be enjoyed and carried out by the village community in the form of community knowledge and awareness as well as an increase in faith which can be seen from the increase in worship activities in the community. This is because in the counseling lectures are also delivered to the people who attend. Tausiah was indeed prepared as one of the approaches to this activity. As a result of follow-up activities it has been reported by local officials that community life shows an increased spirit of community worship. Meanwhile, the spirit to improve the wheels of the economy is also felt to increase. This shows that the impact of community service activities has begun to be felt.